Combination of Solanum nigrum L. Herb Ethanolic Extract and Doxorubicin Performs Synergism on T47D Breast Cancer Cells - Anindyajati, .; Sarmoko, .; Putri, Dyaningtyas D. P.; Hermawan, Adam; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2010)
Leunca (Solanum nigrum L.) has been proven to possessÃÂ  anticancer activity on some type of cancer cells. In vitro study of solamargine found in the herb showed cytotoxic effect against several breast cancer cell lines, such as T47D and MDA-MB-31. Hence, further study on its potential as a co-chemotherapeutic agent needs to be conducted, in order to overcome resistance problem commonly found in cancerÃÂ  chemotherapy. This study aimed to examine the cytotoxic activity of leunca herb ethanolic extract (LEE) alone and its combination with doxorubicin. Single and combinational treatment of LEE and doxorubicin on T47D breast cancer cells were done, and their viability representing cytotoxicity were analyzed by using MTT assay to determine the IC50 value and combination index (CI) to evaluate the combinational effect.ÃÂ  Twenty four hours-treatment of LEEÃÂ  alone gave cytotoxicity activity showing a dose-dependent manner with the IC50 of 47 ÃÂµg/ml, while combinational treatment showed that 4 ÃÂµg/ml LEE was found to be synergist with 4 nM doxorubicin on T47D cells, with the optimum CI value of 0.59. This result shows that Solanum nigrum L. is potential to be proposed as doxorubicin co-chemotherapeutic agent against breast cancer. Further study on its molecular mechanism needs to be conducted.